Market concentration, diversification, and financial distress in the Indonesian banking system - Farida Titik Kristanti; Deannes Isynuwardhana; Sri Rahayu (Jurnal Keuangan dan Perbankan, 2019)
The economic theory provides conflicting predictions about the relationship between the market structure of the banking industry and financial distress. The view of "concentration-fragility" argues that a banking structure that is more concentrated with a number of large banks is more vulnerable to financial fragility than a banking sector that is less concentrated with many banks. We examine how the concentration market, market share, and diversification affect the bank's financial distress. Using the purposive sampling method and data of listed banks in the 2014-2017 period, the results of statistical tests with logistic regression showed that market concentration has a positive effect on the bank’s financial distress. The more concentrated the market, the greater the probability of the occurrence of financial distress in Indonesian banks. We also prove the validity of the SCP (The Structure-Conduct-Performance) hypothesis and efficiency hypothesis. Therefore, regulations need to be made in order to reduce this highly concentrated market so that the probability of financial distress decreases.JEL Classification: D4, G2DOI: https://doi.org/10.26905/jkdp.v23i4.2693